2002
DOI: 10.1098/rstb.2002.1094
|View full text |Cite
|
Sign up to set email alerts
|

Control of plant cytokinesis by an NPK1–mediated mitogen–activated protein kinase cascade

Abstract: Cytokinesis is the last essential step in the distribution of genetic information to daughter cells and partition of the cytoplasm. In plant cells, various proteins have been found in the phragmoplast, which corresponds to the cytokinetic apparatus, and in the cell plate, which corresponds to a new cross wall, but our understanding of the functions of these proteins in cytokinesis remains incomplete. Reverse genetic analysis of NPK1 MAPKKK (nucleus-and phragmoplast-localized protein kinase 1 mitogen-activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Among the poplar MKKs , we found that PtMKK6 is strongly expressed in most of the actively proliferating organs we investigated. Consistent with this, the closest ortholog of PtMKK6 in tobacco, NtMEK1 , encodes a protein that has been shown to be part of a MAPK cascade involved in the progression of the cell cycle [ 62 ]. A similar role has been identified for the Arabidopsis putative ortholog, AtMKK6 [ 13 ], which suggests that MKK6s could be highly conserved players in plant cytokinesis and stem cell development.…”
Section: Discussionmentioning
confidence: 92%
“…Among the poplar MKKs , we found that PtMKK6 is strongly expressed in most of the actively proliferating organs we investigated. Consistent with this, the closest ortholog of PtMKK6 in tobacco, NtMEK1 , encodes a protein that has been shown to be part of a MAPK cascade involved in the progression of the cell cycle [ 62 ]. A similar role has been identified for the Arabidopsis putative ortholog, AtMKK6 [ 13 ], which suggests that MKK6s could be highly conserved players in plant cytokinesis and stem cell development.…”
Section: Discussionmentioning
confidence: 92%
“…To date, only one MAPK signaling pathway with implications in cytoskeletal organization has been largely resolved. This pathway is elemental for the progression of cytokinesis in tobacco (Nicotiana tabacum) and comprises of the NPK1-activating kinesin-like protein 1 (NACK1) and NACK2 Nishihama et al, 2002;Tanaka et al, 2004), the nucleus-and phragmoplast-localized protein kinase 1 (NPK1) Machida, 2000, 2001;Soyano et al, 2002;Takahashi et al, 2004;Tanaka et al, 2004), the NQK1 MAPK kinase (MAPKK), and the NRK1 MAPK (NACK-PQR pathway; Takahashi et al, 2004). It is thought that the activated pathway ultimately targets the tobacco MAP65-1a and 1b isoforms to promote MT dynamics for the expansion of the phragmoplast.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a protein complex comprising nucleus‐ and phragmoplast‐localized MAP3 kinase 1 (NPK1), the NQK1 (next to NPK1) MAP2K and the NRK1 (next to NQK1) MAPK, is transported by two kinesin‐related proteins, namely NACK1 ( N PK1‐ a ctivating k inesin‐like protein 1 ) and NACK2. This signalling pathway, which is termed the PQR pathway of NPK1, NQK1 and NRK1, targets two MT‐associated proteins, namely MAP65‐1a and MAP65‐1b, at the phragmoplast midzone (Nishihama & Machida, 2001; Soyano et al. , 2002; Takahashi et al.…”
Section: Introductionmentioning
confidence: 99%